Mutation Frequency in Main Susceptibility Genes Among Patients With Head and Neck Paragangliomas - Snezhkina, Anastasiya V.; Fedorova, Maria S.; Pavlov, Vladislav S.; Kalinin, Dmitry V.; Golovyuk, Alexander L.; Pudova, Elena A.; Guvatova, Zulfiya G.; Melnikova, Nataliya V.; Dmitriev, Alexey A.; Razmakhaev, George S.; Poloznikov, Andrey A.; Alekseeva, Galina S.; et al. (Frontiers in Genetics, 2020)
Head and neck paragangliomas (HNPGLs) are rare neuroendocrine tumors that have a high degree of heritability and are predominantly associated with mutations in ten genes, such as SDHx, SDHAF2, VHL, RET, NF1, TMEM127, MAX, FH, MEN2, and SLC25A11. Elucidating the mutation prevalence is crucial for the development of genetic testing. In this study, we identified pathogenic/likely pathogenic variants in the main susceptibility genes in 102 Russian patients with HNPGLs (82 carotid and 23 vagal paragangliomas) using whole exome sequencing. Pathogenic/likely pathogenic variants were detected in 43% (44/102) of patients. We identified the following variant distribution of the tested genes: SDHA (1%), SDHB (10%), SDHC (5%), SDHD (24.5%), and RET (5%). SDHD variants were observed in the majority of the patients with bilateral/multiple paragangliomas. Thus, among Russian patients with HNPGLs the most frequently mutated gene was SDHD followed by SDHB, SDHC, RET, and SDHA.